(E)-N-[2-(Biphenyl-4-ylvinyl)phenyl]-furan-2-carboxamide - Ariffin, Azhar; Ng, S.W.; Kee, C.H.; Thomas, N.F.; Awang, Khalijah (International Union of Crystallography, 2008)
In the title molecule, C(25)H(19)NO(2), the furyl ring is twisted by 46.3 (1)degrees with respect to the phenylene ring bearing the amido group. In the stilbene unit, the two phenylene rings (i. e. the rings connected through the - CH = CH - fragment) are twisted by 59.2 (1)degrees; in the biphenylene unit, the two benzene rings are twisted by 35.5 (1)degrees. In the crystal structure, molecules are linked by an N - H ... O amido hydrogen bond into a zigzag chain running along the c axis.